Comprehensive management of blood phosphorus, calcium and parathyroid hormone in patients with chronic kidney disease - XU Gang; GUO Shui-ming; GE Shu-wang (Linchuang shenzangbing zazhi)
The kidney is not only an excretory organ, but also an important organ involved in the regulation of mineral metabolism. Due to the increasing incidence of chronic kidney disease, mineral and bone disorder secondary to chronic kidney disease(CKD-MBD), characterized by imbalances in serum levels of phosphorus, calcium and parathyroid hormone, is also widely concerned. A growing body of clinical evidence suggests that CKD-MBD is significantly associated with quality of life and prognosis in patients with chronic kidney disease. Domestic and international authoritative organizations of nephrology have updated diagnostic and therapeutic guidance related to CKD-MBD. The present article provides an overview of hyperphosphatemia, vascular calcification, hyperparathyroidism and their comprehensive management in patients with CKD-MBD.